2012
DOI: 10.1039/c2ib20076g
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis with nanoPCR

Abstract: Polymerase chain reaction (PCR) has become a standard and important molecular biological technique with numerous applications in genetic analysis, forensics and in vitro diagnostics. Since its invention in the 1980s, there has been dramatic performance improvement arising from long-lasting efforts to optimize amplification conditions in both academic studies and commercial applications. More recently, a range of nanometer-sized materials including metal nanoparticles, semiconductor quantum dots, carbon nanomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…These nanostructures and NPs have been used in areas such as mechanics, optics, biomedical sciences, chemicals, electronics, space industries, drug-gene delivery, energy science, catalysis 1, 2 , optoelectronic devices 3,4 , photo-electrochemical applications 5 , and nonlinear optical devices 6,7 . This strategy afforded potentially powerful PCR technology, with unprecedented sensitivity, selectivity, and extension rates 9,10 . Azmi et al,8 reported the use of ultra-sensitive, silicon nanowire-based biosensor devices for the detection of 8-hydroxydeoxyguanosine (8-OHdG), a biomarker for prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…These nanostructures and NPs have been used in areas such as mechanics, optics, biomedical sciences, chemicals, electronics, space industries, drug-gene delivery, energy science, catalysis 1, 2 , optoelectronic devices 3,4 , photo-electrochemical applications 5 , and nonlinear optical devices 6,7 . This strategy afforded potentially powerful PCR technology, with unprecedented sensitivity, selectivity, and extension rates 9,10 . Azmi et al,8 reported the use of ultra-sensitive, silicon nanowire-based biosensor devices for the detection of 8-hydroxydeoxyguanosine (8-OHdG), a biomarker for prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of DNA is often further evaluated through the use of fluorescence, which uses fluorescent dyes that attach to PCR primers in the amplicons. Reagents used in the PCR process often consist of dimethyl sulfoxide (DMSO), glycerol, formamide, single stranded DNA binding proteins and betaine [38].…”
Section: Polymerase Chain Reaction (Pcr) Amplificationmentioning
confidence: 99%
“…Carbon nanotubes (CNTs), nanometer-sized polymers and silver nanoparticles (AgNPs) have also been able to enhance specificity of PCR. It is theorized that AuNPs are able to work in the same fashion as SSBs, however, the actually mechanism is still under investigation [38]. In particular, microtechnology and nanotechnology have become a method of interest due to the ability to create devices that can prepare, manipulate, and analyze at a very small levels [20].…”
Section: Nanotechnology For Dna Analysismentioning
confidence: 99%
“…The effect of nanomaterials on PCR mainly depends on the strong interaction between PCR components and nanomaterials. 20 However, conflicting results were obtained from different research groups. [21][22][23][24][25] Therefore, the effect of nanomaterials with different surface characteristics on PCR is still unclear and much more systemic and deep investigations are necessary to understand the corresponding mechanism.…”
Section: Introductionmentioning
confidence: 96%